The gold-exchange standard in colonial India: foreshadowing the monetary hierarchy of the international state-credit standard - Vasudevan, Ramaa (Review of international political economy : RIPE, 2024)
This paper investigates how the concrete operation of the gold-exchange standard in colonial India imposed a process of financial subordination embedding colonial India in the currency hierarchy of British sterling. This system was instrumental in entrenching a core-periphery asymmetry that undergirded Britain's financial supremacy, providing elasticity to the sterling funding mechanisms of international money-markets by mobilizing the reserves of colonial India through the council bill mechanism and the placement of reserves in London. Its workings foreshadow the role of reserve accumulation in the financial subordination of developing countries in the context of the dollar hegemony in an international monetary hierarchy delinked from gold and enforced without colonial rule.